A Comparison of Young Publics’ Evaluations of Corporate Social Responsibility Practices of Multinational Corporations in the United States and South Korea - Kim, Daewook; Choi, Myung-Il (2013)
The purpose of this study was to examine how young publics in the United States and South Korea perceive the corporate social responsibility (CSR) practices of multinational corporations and evaluate the effectiveness of CSR practices in terms of organization–public relationship (OPR). Results showed that young publics in the United States and South Korea differently characterized CSR practices of multinational corporations and evaluated relationships with them. Young American participants evaluated the CSR practices of multinational corporations more favorably than did the young Korean participants. In addition, four CSR practices (internal environment, moral, discretionary, and relational) were associated with OPR dimensions in the United States, while only relational CSR practices were significantly related to OPR dimensions in South Korea. Overall, the findings highlight that cultural and societal meanings were embedded in identifying CSR practices and evaluating the relationship with multinational corporations involved in CSR practices.
Keywords: Multinational Corporations; Organization–public relationships; Corporate Social Responsibility